Local Wisdom and Pedagogical Innovation: Integrating Tradition into Modern Learning Practices - Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti; Dewa Gede Bambang Erawan; Ida Ayu Made Wedasuwari; Ketut Alit Pratiwi (Jurnal Pendidikan dan Pengajaran, 2026)
This study investigates the integration of local wisdom into contemporary pedagogical innovations to develop meaningful and culturally sensitive educational practices. A qualitative descriptive methodology was employed, incorporating semi-structured interviews with educators and cultural practitioners, classroom observations, and document analysis. The aim was to understand how cultural traditions are integrated into classroom instruction and the challenges that arise during this process. Research indicates that educators perceive local wisdom as a cultural legacy and a teaching asset that enhances student involvement, moral growth, and cultural identification. Interview excerpts demonstrate that traditional narratives and practices enhance students' engagement and critical thinking skills when integrated with modern approaches, such as project-based learning and digital media. Classroom observations revealed that children engaged more actively when classes incorporated cultural content; however, a document analysis indicated a disparity between policy support for cultural integration and the absence of explicit implementation measures in schools. The study suggests that incorporating local wisdom into pedagogy enhances teaching and learning, but it requires more robust institutional and policy support. The consequence is that education can concurrently equip pupils for global concerns while instilling their cultural values.